Hsa_circ_0062682 Promotes Serine Metabolism and Tumor Growth in Colorectal Cancer by Regulating the miR-940/PHGDH Axis - Sun, Shengbai; Li, Chaoqun; Cui, Kaisa; Liu, Bingxin; Zhou, Mingyue; Cao, Yulin; Zhang, Jia; Bian, Zehua; Fei, Bojian; Huang, Zhaohui (Frontiers in Cell and Developmental Biology, 2021)
Colorectal cancer (CRC) is one of the most common malignancy globally. Increasing evidences indicate that circular RNAs (circRNAs) play a pivotal role in various cancers. The present study focused on exploring the role of a functionally unknown circRNA, hsa_circ_0062682 (circ_0062682), in CRC. By online analyses and experimental validations, we showed that circ_0062682 expression was aberrantly increased in CRC tissues compared with paired normal tissues. Increased expression of circ_0062682 in CRC notably correlated with a poorly prognosis and advanced tumor stage. Functional experiments showed that circ_0062682 knockdown reduced CRC growth both in vitro and in vivo. Mechanistically, we revealed that circ_0062682 could sponge miR-940 and identified that D-3-phosphoglycerate dehydrogenase (PHGDH), a key oxidoreductase involving in serine biosynthesis, as a novel target of miR-940. Silencing miR-940 expression could mimic the inhibitory effect of circ_0062682 knockdown on CRC proliferation. The expression of PHGDH was downregulated in circ_0062682–depleted or miR-940 overexpressing CRC cells at both mRNA and protein levels. Circ_0062682 knockdown suppressed CRC growth by decreasing PHGDH expression and serine production via miR-940. Taken together, these data demonstrate, for the first time, that circ_0062682 promotes serine metabolism and tumor growth in CRC by regulating the miR-940/PHGDH axis, suggesting circ_0062682 as a potential novel therapeutic target for CRC.